2017
DOI: 10.5688/ajpe5989
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition for Empathy, Intercultural Sensitivity, and Intentions for Using Motivational Interviewing in First Year Pharmacy Students

Abstract: Objective. To assess first-year pharmacy (P1) students' predispositions (eg, perceptions for empathy, intercultural sensitivity, and motivational interviewing (MI) as a patient-centered communication skillset) and identify potential curricula content/communication skills training needs. Methods. A cross-sectional survey was used to collect students' self-reported perceptions for empathy, intercultural sensitivity, counseling contexts, and projected future MI use. Relationships between variables were explored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
(46 reference statements)
0
20
1
2
Order By: Relevance
“…19 Some tools used published a validation study which included pharmacy students.19 While other tools had been used in research with pharmacy students evidencing their applicability. 18,[20][21][22][23][24][25][26][27][28][29][30] Additionally, some tools had been validated or used with health care professionals or health care professional students. 15,19,27,[31][32][33][34][35][36][37] Only one tool was identified that assessed cultural competence in the curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Some tools used published a validation study which included pharmacy students.19 While other tools had been used in research with pharmacy students evidencing their applicability. 18,[20][21][22][23][24][25][26][27][28][29][30] Additionally, some tools had been validated or used with health care professionals or health care professional students. 15,19,27,[31][32][33][34][35][36][37] Only one tool was identified that assessed cultural competence in the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the EMC/RSEE, the ISS, and the MEQ may be appealing tools to use to assess pharmacy students early in the curriculum and the CCA later with students when they gain health care experience, but only one study was published for each tool. 29,34,35,37 Reviewing the published literature can also provide insights on how a programs is modifying a tool(s). 44 The IAPCC is a tool that has been used frequently in the literature and it has a student version, but the fee for use may prohibit some programs from adopting it if financial resources are not available.…”
Section: Future Directions For Assessing CCmentioning
confidence: 99%
See 1 more Smart Citation
“…Bizim çalışmamızda birinci ve dördüncü sınıf öğrencilerinin kültürlerarası duyarlılıkları ile merhamet düzeyleri arasında pozitif yönde, dördüncü sınıf öğrencilerinin kültürlerarası duyarlılıkları ile temel empati düzeyleri arasında negatif yönde anlamlı düzeyde bir ilişki saptanmıştır (p<0.05). Eczacılık birinci sınıf öğrencilerle yapılan bir çalışmada öğrencilerin kültürlerarası duyarlılık ve empati eğitimlerine ihtiyaçları olduğu belirlenmiştir (Ekong, Kavookjian ve Hutchison, 2017).…”
Section: Sınıfunclassified
“… 12 Other training methods have also been proposed to enhance medical students’ comprehension of empathy and their empathetic capacity, such as ‘communication skills training’, 13 14 ‘reflective writing’ 15 16 and ‘motivational interviewing training’. 17 While some studies showed that the empathetic capacity of medical students declined with increasing academic years, 18–20 others indicated that the empathy scores of students in their final year were higher than those of first-year medical students. 21 Sex has also been found to influence undergraduate medical students’ empathy.…”
Section: Introductionmentioning
confidence: 99%